Weekend gatherings for bereaved family members after the terror killings in Norway in 2011. Issue 1 (2nd January 2016) - Dyregrov, Atle; Straume, Marianne; Dyregrov, Kari; Grønvold Bugge, Renate
Abstract: This article describes a program to help bereaved families who all lost a close family member during the Utøya terror attacks in Norway where 69 people, mostly of young age, were shot and killed. The bereaved gathered over four weekends to process and learn about grief in a program organised by the Norwegian Directorate of Health (NDH). This proactive follow-up included bereaved parents and siblings who took part in group sessions, plenary lectures, workshops, and social activities over four weekends following the terror killings. The same structure was used in each gathering. The themes, both in groups and plenary, changed over time and reﬂected important events (eg. the trial, verdict, commission report) and the grief process over time. A tentative evaluation by the NDH indicated that the bereaved found this approach very helpful. The description provides a 'blueprint' that can be a starting point for organising future follow-up for bereaved people after disasters.